Ultra-fast 1+1 protection in 10 Gb/s symmetric long reach PON - PAYNE, DAVID; RUFFINI, MARCO; MCGETTRICK, SÉAMAS (IET, 2013)
In this paper we evaluate PON protection switching times using our FPGA-based hardware implementation of a Long-Reach PON protocol based on the XGPON standard. We first compare reactivation times of different 1+1 protection scenarios, and then we propose hardware modifications to reduce PON protection times
IET Conference Publications
39th European Conference and Exhibition on Optical Communication, ECOC 2013
PUBLISHED
London
Keywords: PON protection switching times